DOMINASI SIMBOLIK DALAM PENEGAKAN HUKUM PIDANA BERDASARKAN PERSPEKTIF PIERRE-FELIX BOURDIEU - Marbun, Rocky (Esensi Hukum, 2021)
Refining activities Legal Studies as a science that is sui generis, in the end, have exposed a pattern of reasoning and legal arguments against the concrete fact to be very rigid and lexical. In fact, law that emerges from a social agreement and grows together with the development of society, has taken a distance (distantiation) from society, which is the origin of the growth of the law itself. It is Pierre-Felix Bourdieu who argues that every social praxis (action) - including the behavior of law enforcers, will always produce knowledge based on legal norms and power - as capital, through the absorption of values that internalize in themself (habitus). This research is a normative legal research with a statutory approach, a conceptual approach, a semiotic approach, and a critical discourse analysis approach. The results of this study indicate the consequences that occur through symbolic domination as doxa to defend the interests of the executive law enforcement agency.